2015
DOI: 10.2340/16501977-1937
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic circuit training including aqua-cycling in patients with knee osteoarthritis: A feasibility study

Abstract: An aquatic circuit training that includes aqua- cycling is feasible for patients with knee osteoarthritis. Participants reported pain reduction and were positive about the diverse exercise programme. Aqua-cycling in a seated position is a safe and controlled type of movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 7 publications
6
11
2
1
Order By: Relevance
“…Our results are somewhat supportive of the feasibility of home-based HIIT and MICT cycling programs for middle-aged and older adults with knee OA, with the enrolment rate and adherence rate for both the HIIT and MICT groups comparable to other cycling studies involving similar populations (Alkatan et al 2016;Rewald et al 2015;Salacinski et al 2012). The number of adverse events (HIIT: 2 of 9 participants, 26 adverse events; MICT: 1 of 8 participants, 2 adverse events) appeared very high, although 24 of these adverse events were reported by one HIIT individual with a Bakers cyst on their knee, who still completed 25 of the requested 32 exercise sessions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results are somewhat supportive of the feasibility of home-based HIIT and MICT cycling programs for middle-aged and older adults with knee OA, with the enrolment rate and adherence rate for both the HIIT and MICT groups comparable to other cycling studies involving similar populations (Alkatan et al 2016;Rewald et al 2015;Salacinski et al 2012). The number of adverse events (HIIT: 2 of 9 participants, 26 adverse events; MICT: 1 of 8 participants, 2 adverse events) appeared very high, although 24 of these adverse events were reported by one HIIT individual with a Bakers cyst on their knee, who still completed 25 of the requested 32 exercise sessions.…”
Section: Discussionsupporting
confidence: 80%
“…The sample size was also relatively small, which may affect our ability to detect within and between group significant differences and the potential generalisability of the trial findings. Nevertheless, the sample size in the study was greater (Rewald et al 2015)…”
Section: Manuscript To Be Reviewedmentioning
confidence: 97%
“…It might also an option for patients who feel uncomfortable with traditional aquatic exercise because of poor swimming skills or hydrophobia. Previous studies have shown that aqua-cycling is well accepted by patients who have hydrophobia [ 22 , 24 ]. As aqua-cycling has become a recent fitness trend in Europe and the US, many public swimming pools offer aqua-spinning to a healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a conditioning phase of 25 min, this is an increase of 1 % per week, which is lower than the recommended weekly increase of 2.5 % as advocated by the American Geriatric Society [ 33 ]. This is deliberate, however, as the assumption is that aqua-cycling is more demanding than stationary cycling on land [ 24 , 33 ]. Increased pedalling resistance was offered with caution and only if a participant was able to cycle continuously at 60 rpm without adverse reactions such as increased knee pain after the session, because increased workload results in increased knee load.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation